Passive corrosion of steel reinforcement in blended cement-based material in the context of nuclear waste disposal. (28th April 2017) - Chomat, Laure; Amblard, Etienne; Varlet, Jérôme; Blanc, Cécile; Bourbon, Xavier
ABSTRACT: An experimental campaign was carried out to study the passivity of steel embedded in blended cement paste. Mockup samples made of steel coupons (milled or pre-corroded) embedded in cement paste were tested under controlled relative humidity or in a solution simulating clay underground water and under aerated and de-aerated conditions, during up to 3 years. The results of gravimetric measurements show that the average corrosion rates determined on milled coupons are lower than 1 µm/year and vary from 0.2 to 2.7 µm/year for pre-corroded coupons. An apparent passive corrosion state is reached rapidly whatever the environmental conditions. Moreover, solid characterisations (Raman spectroscopy and SEM-EDS) point to a stable state in terms of the nature of the corrosion products and of the composition of the steel/cement paste interface. These results are similar to the ones previously obtained for steel coupons embedded in Portland cement mortar. This paper is part of a supplement on the 6th International Workshop on Long-Term Prediction of Corrosion Damage in Nuclear Waste Systems.